Handbook on Poverty and Inequality - Haughton, Jonathan; Khandker, Shahidur R. (Washington, DC: World Bank, 2012)
The handbook on poverty and inequality provides tools to measure, describe, monitor, evaluate, and analyze poverty. It provides background materials for designing poverty reduction strategies. This book is intended for researchers and policy analysts involved in poverty research and policy making. The handbook began as a series of notes to support training courses on poverty analysis and gradually grew into a sixteen, chapter book. Now the Handbook consists of explanatory text with numerous examples, interspersed with multiple-choice questions (to ensure active learning) and combined with extensive practical exercises using stata statistical software. The handbook has been thoroughly tested. The World Bank Institute has used most of the chapters in training workshops in countries throughout the world, including Afghanistan, Bangladesh, Botswana, Cambodia, India, Indonesia, Kenya, the Lao People's Democratic Republic, Malawi, Pakistan, the Philippines, Tanzania, and Thailand, as well as in distance courses with substantial numbers of participants from numerous countries in Asia (in 2002) and Africa (in 2003), and online asynchronous courses with more than 200 participants worldwide (in 2007 and 2008). The feedback from these courses has been very useful in helping us create a handbook that balances rigor with accessibility and practicality. The handbook has also been used in university courses related to poverty.